IMPLEMENTASI PASAL 183 PERATURAN MENTERI LINGKUNGAN HIDUPDAN KEHUTANAN NOMOR 9 TAHUN 2021 TENTANG PENGELOLAANPERHUTANAN SOSIAL DI DESA PULAU PADANG KABUPATENKUANTAN SINGINGI - Tri Asih Sukma Sari; Mexsasai Indra; Evi Deliana HZ (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Forests are a source of life for all living things, especially for communitiesaround the forest. With the birth of a social forestry policy, the government hopesto improve the standard of living of the economy and maintain the sustainability offorest areas. In implementing policies, supervision is needed in their management.In Kuantan Singingi Regency, it is one of the areas that received social forestrylicenses. However, the management of social forestry is still not optimal. This canbe seen from the still minimal area of social forestry so that there are still thosewho have not carried out management since the decree was issued, therefore thegovernment's attention is needed so that the objectives of targeted management canbe achieved. The type of research used is sociological legal research. Obstacles insupervising social forestry in Kuantan Singingi Regency include: Lack ofoperational staff, lack of budget, convoluted administrative reporting, lack ofcoordination of related parties, and lack of public knowledge of social forestry. Thesolutions provided include: adding operational personnel such as assistants,encouraging local government budgets in facilitating the implementation ofsupervision, increasing collaboration with PPS Working Groups, providingeducation to the community and assistants so that they can help people inmanagement and prevent forest utilization that is not in accordance with existingregulations .Keyword: Implementation-Social Forestry-Supervation